1993
DOI: 10.1002/mus.880160603
|View full text |Cite
|
Sign up to set email alerts
|

Acute conduction block in vitro following exposure to antiganglioside sera

Abstract: We studied the role of antiganglioside antibodies in the pathogenesis of autoimmune neuropathies using an in vitro preparation of a rat sciatic nerve. Human and rabbit sera with high titers of the antibodies were applied to a restricted segment of the sciatic nerve mounted in a recording chamber, and the compound nerve action potentials of the myelinated and unmyelinated fibers were observed. Myelinated fiber conduction became blocked at the segment within a few hours, whereas the unmyelinated fiber conduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(30 citation statements)
references
References 23 publications
1
27
1
1
Order By: Relevance
“…With respect to the antibody induction phase of the illness, it is clearly established that anti-GM1 antibodies can arise through molecular mimicry with structurally homologous Campylobacter jejuni lipooligosaccharides (LOS) (15)(16)(17)(18). In contrast, examination of the effector pathways through which anti-GM1 antibodies selectively bind to and induce injury in motor nerve membranes, while avoiding damage to other neural and non-neural plasma membranes containing abundant GM1, is confounded by inconsistent and often counterintuitive data (9,(19)(20)(21)(22). In particular, the sensitivity or resistance of the membrane toward undergoing anti-GM1 antibody-mediated injury cannot be fully explained by the presence and density of plasma membrane GM1.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the antibody induction phase of the illness, it is clearly established that anti-GM1 antibodies can arise through molecular mimicry with structurally homologous Campylobacter jejuni lipooligosaccharides (LOS) (15)(16)(17)(18). In contrast, examination of the effector pathways through which anti-GM1 antibodies selectively bind to and induce injury in motor nerve membranes, while avoiding damage to other neural and non-neural plasma membranes containing abundant GM1, is confounded by inconsistent and often counterintuitive data (9,(19)(20)(21)(22). In particular, the sensitivity or resistance of the membrane toward undergoing anti-GM1 antibody-mediated injury cannot be fully explained by the presence and density of plasma membrane GM1.…”
Section: Introductionmentioning
confidence: 99%
“…We show that the antibody binds to a wide range of peripheral nerve structures and induces electrophysiological abnormalities in mouse nerve compatible with its putative pathophysiological effects on the human peripheral nervous system (PNS). Previous animal studies using antiganglioside antibodies to induce experimental neuropathy using whole sera or partially purified sera (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) have also shown immunopathogenic effects. These data lend great support to the view that antiganglioside antibodies have the capacity to induce autoimmune neurological disease.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that high titers of anti-GM l antisera from rabbits immunized with GM1ganglioside induce impairment of action potential with an accompanying decrease in Na+currents and an increase in K+currents in rat myelinated nerve fibers (6). However, there have been controversial results on the effect of anti-GMl antibody on nerve fibers and neurons (7)(8)(9). This may be partly due to the different methods which each study used.…”
Section: Introductionmentioning
confidence: 99%